2000
DOI: 10.1007/s004150070113
|View full text |Cite
|
Sign up to set email alerts
|

PMP22 Thr118Met is not a clinically relevant CMT1 marker

Abstract: It is controversial if peripheral myelin protein 22 gene (PMP22) Thr118Met represents a functionally irrelevant polymorphism or, since hemizygosity for this variant has been found in two patients with Charcot-Marie-Tooth disease type 1 (CMT1 patients), it can act as a recessive CMT1 mutation. To shed further light on this variant and its diagnostic value we searched for carriers in 1018 individuals from the German general population, in 104 probands with hereditary neuropathy with liability to pressure palsies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…However, the clinical relevance of the T118M variant of the PMP22 gene has been controversial. Several studies have suggested that it may be autosomal recessive [2], partial loss of function [810], or a benign variant [11]. In this study, we report three cases in support that the T118M variant of the PMP22 gene is a partial loss of function mutation rather than a benign variant.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…However, the clinical relevance of the T118M variant of the PMP22 gene has been controversial. Several studies have suggested that it may be autosomal recessive [2], partial loss of function [810], or a benign variant [11]. In this study, we report three cases in support that the T118M variant of the PMP22 gene is a partial loss of function mutation rather than a benign variant.…”
Section: Introductionsupporting
confidence: 53%
“…However, other studies presented data in support of it being a deleterious variant. The largest study is a case-control study with 1018 healthy subjects, 104 unrelated patients with hereditary neuropathy with liability to pressure palsies (HNPP), and 187 patients with Charcot-Marie-Tooth disease type 1 (CMT1) [11]. It found T118M to be associated with CMT1A without the 1.5-Mb duplication (P=0.0429), but not associated with HNPP or CMT1 with the 1.5Mb duplication.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the other patients in that study, who carried a heterozygous T118M PMP22 mutation, developed HNPP 16. In other studies, the T118M substitution was found in 1.4% of healthy controls in a German population and 1.9% in a Swedish population, and thus it was unclear whether it was a benign polymorphism or a recessive CMT mutation 17, 18…”
Section: Discussionmentioning
confidence: 71%
“…Roa et al (2) interpreted it as a recessive condition, since a patient carrying a 17p11.2-p12 deletion in one chromosome and this point mutation in the other one expressed a severe CMT1 phenotype, while her younger son who carried only the Thr(118)Met allele was phenotypically normal, and her two older boys who inherited the deleted chromosome manifested a mild HNPP phenotype. A second similar pedigree was found (3) supporting this initial idea, that was questioned by the case described by Young et al (6), in which the hemizygous patient with the Thr(118)Met mutation did have the usual HNPP phenotype. Nelis et al (4) raised the possibility that this substitution could just be a polymorphism as they found an allele frequency of 0.019 in a study on 262 control individuals from the Swedish population.…”
Section: Discussionmentioning
confidence: 96%